Anaesthetic management for laparoscopic cholecystectomy in a child - Nishant, Kumar; Bhattarai, Balkrishna; Adhikary, Shailesh (Journal of Society of Anesthesiologists of Nepal, 2014)
Laparoscopic surgical techniques offer several advantages over conventional open surgery. However, anaesthesia for laparoscopic surgical procedures is challenging due to various associated physiological consequences mainly of intra-peritoneal carbon dioxide insufflation and positioning. Gall stone disease is rare in pediatric age group and therefore, experience of anaesthetic management in such a condition is limited. Here we describe anaesthetic management of a 56-month-old male child scheduled for laparoscopic cholecystectomy for gall stone disease.